Collaborative writing using wiki: Tertiary students’ perspectives - Joseph, Ramanair; Rethinasamy, Soubakeavathi; Jecky, Misieng (National University of Singapore, 2017)
Technology offers much potential to language pedagogy. In particular, the use of Wiki, which is part of Web 2.0 technology, is often recommended as a tool to support students’ writing activities. This study explored undergraduate students’ reactions to the use of Wiki for a group academic writing assignment. It involved 50 undergraduate students at a public university in Malaysia. Students’ views were obtained through a questionnaire, which consisted of a set of closed-ended questions and open-ended questions. The questionnaire items focused on four aspects, which are Interaction, Ease of Use, Satisfaction, and Motivation. The findings revealed that the use of Wiki enabled the group members to interact and there was a sense of satisfaction with the use of the Wiki in supporting their academic writing. The students’ experience in using Wiki motivated them to explore its use and also to recommend it to their friends. However, several issues related to the ease of use impeded the effective use of the Wiki. The analysis of the data from the open-ended questions shed some light on the challenges these students experienced in using Wiki for academic writing. © Centre for Language Studies National University of Singapore.